BIAS GENDER DALAM PROSES PENDIDIKAN ISLAM - Jelli Gustiana (Marwah: Jurnal Perempuan, Agama dan Jender, 2014)
Education is an activity that is carried out in the community with the goal of humanizing. Formal education is a means for socialization and transfer of values and norms prevailing in society, including the values and norms of gender. There was a lot of gender inequalities in society that arises because there is a gender bias in education including religious education. Based on the search turns gender inequality in education is not because of the substance of religion, but rather the interpretation misunderstood an original source of religion (Islam), thus the need reintepretasi religious understanding of gender bias is continuous, improve education curriculum that eliminates dichotomous between men and women, and provide higher learning opportunities to women